Political Selection and Bureaucratic Productivity - Habyarimana, James; Khemani, Stuti; Scot, Thiago (World Bank, Washington, DC, 2018)
Economic theory of public bureaucracies as complex organizations predicts that bureaucratic productivity can be shaped by the selection of different types of agents, beyond their incentives. This theory applies to the institutions of local government in the developing world, where nationally appointed bureaucrats and locally elected politicians together manage the implementation of public policies and the delivery of services. Yet, there is no evidence on whether (which) selection traits of these bureaucrats and politicians matter for the productivity of local bureaucracies. This paper addresses the empirical gap by gathering rich data in an institutional context of district governments in Uganda, which is typical of the local state in poor countries. The paper measures traits such as the integrity, altruism, personality, and public service motivation of bureaucrats and politicians. It finds robust evidence that higher integrity among locally elected politicians is associated with substantively better delivery of public health services by district bureaucracies. Together with the theory, this evidence suggests that policy makers seeking to build local state capacity in poor countries should take political selection seriously.